A Phonological Study of the Metrical Structure of Some Iraqi Arabic Nursery Rhymes - Balqis Issa Gatta ___ Mariam Naeem Hassan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The present study attempts to analyze the metrical patterns of Iraqi Arabic nursery rhymes. The study specifically deals with assigning the word stress patterns according to Hayes’s (1995) metrical theory. The core assumption of this theory is that “stress is a hierarchy of rhythmic patterns in which one syllable scores relative prominence with relation to an adjacent one” (Al.Abdely 2011, p.379). The results reveal that the disyllabic words and also the dimeter lines are frequent types of the analyzed three IA nursery rhymes.